Bioconjugation of a Fibroblast Activation Protein Targeted Interleukin-4 - Ruopp, Matthias; Zhu, Sha; Worschech, Rafael; Haas, Dorothee; Maschauer, Simone; Prante, Olaf; Meinel, Lorenz; Lühmann, Tessa (ACS Biomaterials Science and Engineering, 2023)
Interleukin-4 (IL-4) is an immune-modulating therapeutic with growing potential for the treatment of inflammatory diseases. Current challenges of IL-4 therapy include a low serum half-life and pleiotropic activity, suggesting effective targeting of IL-4. To develop an interleukin-4 bioconjugate with rapid targeting to inflammatory disease sites, we report the chemical synthesis, bioconjugation, and in vitro characterization of a murine interleukin-4 (mIL-4) conjugate decorated with a fibroblast activation protein inhibitor (FAPI). The FAPI targeting moiety features 2,2′,2″,2‴-(1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayl)tetraacetic acid (DOTA) to allow future biodistribution and imaging studies of the FAPI-mIL-4 bioconjugate. We demonstrated site-specific coupling of mIL-4 and FAPI-DOTA deploying chemo-enzyme and enzyme chemistries with a high purity exceeding 95%. The FAPI-DOTA modified mIL-4 was bioactive with polarization of murine macrophages into the M2 state while maintaining specific binding to FAP on fibroblast cells. Together, these results point to future in vivo use of the FAPI-mIL-4 bioconjugate to assess biodistribution and biological effects in animal models of inflammatory joint disease.
CRIS-Team Scopus Importer:2023-11-03
Keywords: genetic code expansion; fibroblast activation protein; interleukin-4; macrophage polarization; bioconjugation